Kinetics of Photocatalytic Degradation of p-Toluene Sulfonic Acid on TiO2 Surface - Cao*, Hongxia; Feng, Qingzhen (Asian Journal of Chemistry, 2013)
In present work, the photocatalytic degradation of p-toluene sulfonic acid was investigated in aqueous solutions containing TiO2 suspension as photocatalyst, especially the kinetics was discussed. The effects of the various operating parameters including initial concentration of p-toluene sulfonic acid, pH value, TiO2 concentration and irradiation intensity etc., were studied. Results showed that the kinetics of photocatalytic degradation of p-toluene sulfonic acid in the presence of TiO2 was in accord with first-order Langmuir-Hinshelwood model when the initial concentration of p-toluene sulfonic acid was lower than 100 mg/L. The apparent degradation rate constants decreased with increase of the initial concentration of p-toluene sulfonic acid and displayed with one-peak pattern with the increases of TiO2 concentration and aqueous pH value. As the increasing concentration of p-toluene sulfonic acid, a trend that the degradation reaction transferred from first-order to zeroth-order reaction model was observed. The optimal operating parameters were consisted of pH at 3 and TiO2 of 100 mg/L. It was also observed that the presence of air could accelerate the degradation rate dramatically.